Does the chick of domestik chicken (Gallus gallus domesticus) in early development would able to witstand the injection of crude LPS? - lelono, Asmoro; Laensugi, Agatha Dei Gratia; Arimurti, Sattya (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2024)
Preventing bacterial infections in poultry farms is a key aspect of effective disease management strategies. Enhancing innate immunity serves as a vital preventive measure in chicken farming. Lipopolysaccharide (LPS), a fundamental component of the bacterial cell wall, has been successfully utilized to boost the innate immune response in susceptible poultry hosts. This study focused on examining the impact of administering crude LPS from Salmonella typhimurium to a domestic chicken (Gallus gallus domesticus) strain during its early developmental stages up to the pre-maturation phase. Immune responses in the chicks were evaluated by observing changes in body temperature and leukocyte differentiation. The chickens were divided into two groups: control (injected with 0.85% NaCl) and treatment (injected with the LPS). The injections were applied in three different ages 7 days, 24 days, and 41 days. The body temperature and leukocyte differential data were collected following the LPS injection. Results showed a significant difference in body temperature and heterophil at the ages of 24 and 41, indicating an immune response characterized by inflammation and elevated heterophil levels. There was a significant increase in basal temperature during early development in line with chicks' development to maintain their homeostatic system. This study concludes that the chicks demonstrated resilience to the presence of LPS by exhibiting heightened responses. The increasing of heterophils concentration provided strong evidence of their immune capability to overcome bacterial infections